2019
DOI: 10.1111/nph.15936
|View full text |Cite
|
Sign up to set email alerts
|

Brassinosteroid regulation of wood formation in poplar

Abstract: Summary Brassinosteroids have been implicated in the differentiation of vascular cell types in herbaceous plants, but their roles during secondary growth and wood formation are not well defined. Here we pharmacologically and genetically manipulated brassinosteroid levels in poplar trees and assayed the effects on secondary growth and wood formation, and on gene expression within stems. Elevated brassinosteroid levels resulted in increases in secondary growth and tension wood formation, while inhibition of br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 55 publications
4
46
0
Order By: Relevance
“…2). Hence, our results indicated that PtoDET2 could significantly increase BRs level for much enhanced plant growth and biomass yield, consistent with the previous findings that BRs-related genes could promote plant growth [31][32][33][34][35][36][37][38][39][40].…”
Section: Ptodet2 Overexpression Improved Plant Growth and Biomass Yiesupporting
confidence: 92%
See 4 more Smart Citations
“…2). Hence, our results indicated that PtoDET2 could significantly increase BRs level for much enhanced plant growth and biomass yield, consistent with the previous findings that BRs-related genes could promote plant growth [31][32][33][34][35][36][37][38][39][40].…”
Section: Ptodet2 Overexpression Improved Plant Growth and Biomass Yiesupporting
confidence: 92%
“…Compared to the WT, the PtoDET2-OE transgenic lines exhibited much expanded xylem area with significantly increased stem diameter and amounts of xylem cell layers as well as larger vessel/fiber cells ( Fig. 3a, b), in agreement with the previous reports that BRs promote differentiation of xylem cells [33][34][35]. Accordingly, we detected significantly increased transcription levels of four representative genes involved in xylem cell differentiation and expansion (Additional file 1: Fig.…”
Section: Ptodet2 Affected Wood Formation and Wall Polysaccharides Biosupporting
confidence: 90%
See 3 more Smart Citations